Retrospective study of RAS/PIK3CA/BRAF tumor mutations as predictors of response to first-line chemotherapy with bevacizumab in metastatic colorectal cancer patients. Issue 1 (December 2017) - Nakayama, Izuma; Shinozaki, Eiji; Matsushima, Tomohiro; Wakatsuki, Takeru; Ogura, Mariko; Ichimura, Takashi; Ozaka, Masato; Takahari, Daisuke; Suenaga, Mitsukuni; Chin, Keisho; Mizunuma, Nobuyuki; Yamaguchi, Kensei
Abstract Background After analysis of minorRAS mutations (KRAS exon 3, 4/NRAS ) in the FIRE-3 and PRIME studies, an expanded range ofRAS mutations were established as a negative predictive marker for the efficacy of anti-EGFR antibody treatment.BRAF andPIK3CA mutations may be candidate biomarkers for anti-EGFR targeted therapies. However, it remains unknown whetherRAS/PIK3CA/BRAF tumor mutations can predict the efficacy of bevacizumab in metastatic colorectal cancer. We assessed whether selection according toRAS/PIK3CA/BRAF mutational status could be beneficial for patients treated with bevacizumab as first-line treatment for metastatic colorectal cancer. Methods Of the 1001 consecutive colorectal cancer patients examined forRAS, PIK3CA, andBRAF tumor mutations using a multiplex kit (Luminex®), we studied 90 patients who received combination chemotherapy with bevacizumab as first-line treatment for metastatic colorectal cancer. The objective response rate (ORR) and progression-free survival (PFS) were evaluated according to mutational status. Results The ORR was higher among patients with wild-type tumors (64.3%) compared to those with tumors that were only wild type with respect toKRAS exon 2 (54.8%), and the differences in ORR between patients with wild-type and mutant-type tumors were greater when considering onlyKRAS exon 2 mutations (6.8%) rather thanRAS/PIK3CA/BRAF mutations (18.4%). There were no statistically significant differences in ORR or PFS between all wild-type tumors and tumors carrying any of the mutations. Multivariate analysis revealed that liver metastasis andRAS andBRAF mutations were independent negative factors for disease progression after first-line treatment with bevacizumab. Conclusions Patient selection according toRAS/PIK3CA/BRAF mutations could help select patients who will achieve a better response to bevacizumab treatment. We found no clinical benefit of restricting combination therapy with bevacizumab for metastatic colorectal cancer patients with EGFR-wild type tumors.